Early impairment of food intake in patients newly diagnosed with cancer - Molfino, Alessio; Emerenziani, Sara; Tonini, Giuseppe; Santini, Daniele; Gigante, Antonietta; Guarino, Michele Pier Luca; Nuglio, Chiara; Imbimbo, Giovanni; La Cesa, Annalisa; Cicala, Michele; Muscaritoli, Maurizio (Frontiers in Nutrition, 2023)
Background Patients with gastrointestinal or lung cancer often suffer from a loss of appetite (anorexia), resulting in reduced food intake (hypophagia) and body weight loss. This study evaluated the prevalence of anorexia, hypophagia, pre-cachexia and cachexia in patients with cancer at time of diagnosis. Patients and Methods Patients with newly diagnosed gastrointestinal or lung cancers were included. Body mass index (BMI) and weight loss over the prior 6 months were recorded. Patients were assessed for (pre-)cachexia and for anorexia using the Functional Assessment of Anorexia/Cachexia Therapy (FAACT) and a specific anorexia questionnaire (AQ). Energy and protein intake were calculated through food diaries. Patients were considered hypophagic if intake was ≤70% of guideline-recommended levels. Results Overall, 102 patients (53 male; median age: 67 [range, 21–88] years) were enrolled. Mean BMI (±standard deviation) was 23.1±3.4 kg/m2; average percentage of weight loss was 10.1±7.8%. At diagnosis, 68% (69/102) of patients had cachexia, and 11% (11/102) pre-cachexia. Prevalence of anorexia was 57% (58/102) and 75% (76/102) according to FAACT and AQ, respectively. Forty-eight percent (49/102) of patients had hypophagia. Patients with anorexia had lower daily energy (p=0.002) and protein intake (p=0.0257), and greater percentage of weight loss (p=0.0005). In patients with hypophagia, negative correlations were observed between percentage of weight loss and total daily calorie (r=-0.40; p=0.01) and protein intake (r=-0.340; p=0.018). Conclusion Anorexia, inadequate nutritional intake and cachexia are highly prevalent in patients with gastrointestinal or lung cancer at diagnosis. Negative protein and energy balance may play an important role in the pathogenesis of cachexia. Early multimodal strategies to improve food intake are urgently needed.